Root growth dynamics and productivity of quinoa (Chenopodium quinoa Willd.) in response to fertilization and soil tillage - Kakabouki Ioanna P.; Roussis Ioannis; Hela Dimitra; Papastylianou Panayiota; Folina Antigolena; Bilalis Dimitrios (Folia Horticulturae, 2019)
Quinoa is a gluten-free pseudocereal crop recognized for its exceptional nutritional properties. A 3-year field experiment was conducted to evaluate the influence of soil tillage and fertilization on root growth and productivity of quinoa. The experiment was laid out in a split-plot design with two replicates, two main plots [conventional (CT) and minimum tillage (MT)] and four sub-plots [fertilization treatments: untreated, inorganic fertilization with 100 (N1) and 200 kg N ha−1 (N2), and sheep manure]. Mean weight diameter (MWD) of soil aggregates, total porosity, organic matter and soil total nitrogen increased with the long-term fertilization with sheep manure. The major part of the roots (approximately 70%) is concentrated in the 0-30 cm soil layer. Root length density increased with increased rate of applied nitrogen, and a higher value (1.172 cm cm−3) was found in N2 plots. Additionally, higher root mass density (1.114 mg cm−3) was observed under MT. Plant height and dry weight were clearly affected by fertilization, with higher values obtained in N2 plots. Moreover, it was observed that quinoa cultivated under CT and N2 treatment produced a higher seed yield (2595 kg ha−1). As a conclusion, increasing the levels of applied nitrogen up to 200 kg N ha−1 improves root growth and consequently the yields of quinoa.